PERLAWANAN SIMBOLIK TERHADAP ORDE BARU DALAM NOVEL HARIMAU!HARIMAU!KARYA MOCHTAR LUBIS (KAJIAN HEGEMONI) - Sujito Sujito (EDU-KATA, 2014)
The study focuses on the symbolic resistance of the New Order with data sources of MochtarLubis’ novel Harimau! Harimau! or Tiger! Tiger! In English. The novel emphasizes symbolic meaning of the same ferocity between a tiger and leader of the New Order in Indonesia. In the novel the story is shown three types of human character WakKatok, Pak Haji Rahmat, and Buyung are often encountered in social and political history of the New Order. WakKatokas a leader who is mystical, propaganda, hypocritical, unfair and oppressive. In fact, He is just a coward and only for personal interest. Based on this background, Itformulates four research problems. The four research problems are: (1) Howdoes the New Order government instill an ideology to the people in MochtarLubis’ novel Tiger! Tiger!?; (2) What kinds of popular resistance against theNew Order government in the MochtarLubis’ novel Tiger! Tiger!?, (3) What is the impact of the dominance of New Order regimetowards people life in the novel Tiger! Tiger! ?; (4) How does the resistance of the people against the New Order regime's disobedience in MochtarLubis’ novel Tiger! Tiger!?; Based on these four issues, the aims of this research is to find: (1) How to instill the ideology of the New Order regime, (2) The forms of popular resistance against the New Order regime, (3) Impact of the New Order regime domination in the people's lives, (4) Resistance to the law disobedience of the people against the New Order regime. Technique used in data analysis is the interactive analysis technique that is reduced data, exposured data, and inference proceeds into a mutual entity. Data analysis techniques with methods of hermeneutic framework.